Cleaner pad-steam dyeing technology for cotton fabrics with excellent utilization of reactive dye. (20th December 2019) - Shu, Dawu; Fang, Kuanjun; Liu, Xiuming; Cai, Yuqing; An, Fangfang; Qu, Ge; Liang, Yingchao
Abstract: Developing a high utilization dyeing approach for cotton fabrics coloring is essential for the textile production in view of economic and ecological reasons. To enhance dye utilization and alleviate environment pollution, an industrializable pre-diffusion technique was applied to traditional pad-steam dyeing to enhance the effective reactions between fibers and reactive dyes. The appropriate dyeing conditions were determined. Dyeing mechanism was revealed by analyzing the speckle rates and reactive dye distribution within the padded fabrics. Dyeing properties, chemicals and energy consumptions, dyeing wastewater absorbance were measured and compared with conventional pad-steam dyeing. The appropriate dyeing conditions were recommended as follows: the padded fabrics were placed at 30 °C for 120 min to complete the pre-diffusion, and then fixed in atmospheric saturated steam for 4 min. The variation of speckle rates verified the change in free water of padded fabrics. Fabric cross-section indicated that the pre-diffusion procedure could improve reactive dye distribution. The recommended technology presented superior dyeing properties including dark color, high dye utilization and satisfactory color fastness. The reduction of about 8% dye, 12.5% Na2 CO3 and 20% steam can be achieved using the developed dyeing technology. The absorbance of washing liquor using the recommended process was 0.29, about 65.9% lower than that of conventional pad-steam dyeing. The developed dyeing technology has distinct advantages of high dye utilization and lowly-colored dyeing wastewater discharge, which is conducive to saving chemicals and protecting the environment. Graphical abstract: Image 1003481 An industrializable pre-diffusion technique was applied to conventional pad-steam dyeing to enhance dye utilization and alleviate environment pollution. Highlights: A cleaner pad-steam dyeing technology with high dye utilization was developed. Excellent color performance and crocking fastness of dyed fabrics are obtained. The savings of 8% dye, 12.5% Na2 CO3 and 20% steam can be achieved.